Hospital Surge Preparedness and Response Index. (June 2021) - Thomasian, Nicole M.; Madad, Syra; Hick, John L.; Ranney, Megan L.; Biddinger, Paul D.
Abstract: The Hospital Surge Preparedness and Response Index is an all-hazards template developed by a group of emergency management and disaster medicine experts from the United States. The objective of the Hospital Surge Preparedness and Response Index is to improve planning by linking action items to institutional triggers across the surge capacity continuum. This responder tool is a non-exhaustive, high-level template: administrators should tailor these elements to their individual institutional protocols and constraints for optimal efficiency. The Hospital Surge Preparedness and Response Index can be used to provide administrators with a snapshot of their facility's current service capacity in order to promote efficiency and situational awareness both internally and among regional partners.